Concerted practices and agreements in European Union competition law - Kayhan, Fatih (My University, 2001)
Bu tezin temel konusunu Avrupa Topluluğu Antlaşmasının 81(1). Maddesinde yer alan 'Anlaşmalar' ve 'Uyumlu Eylemler' oluşturmaktadır. 'Teşebbüs Birlikleri Kararları' da tez kapsamında açıklanmıştır. Kurucu Antlaşma, Avrupa Birliği Rekabet Hukuku bakımından önemli hedefler koymuş, Avrupa Topluluğunun serbest piyasa sistemi üzerine kurulmasını öngörmüştür. Bu bağlamda etkin bir rekabet sisteminin tesis edilmesi, ortak pazarın gerçek anlamıyla meydana getirilebilmesi için gerekli olmuş, Avrupa Topluluğu Antlaşmasının 81. ve 88. maddeleri arasında düzenlenen rekabete ilişkin kurallar da bu çerçevede önem kazanmıştır. Avrupa Topluluğu Antlaşmasının 81(1). Maddesine göre; Tek Pazar içerisinde rekabeti kısıtlayan, engelleyen veya bozan amaç veya konuya sahip olan veya bu etkiyi yapan teşebbüsler arasındaki anlaşmalar, teşebbüs birlikleri kararları ve uyumlu eylemler hukuka aykırı görülmüştür. 81(1). madde kapsamında rekabetin bozulmasının koşulları şunlardır; a) Teşebbüsler arasında danışıklık olması gereklidir, b) Bu danışıklık rekabetin kısıtlanması, bozulması veya engellenmesi amaçlı veya etkili olmalıdır, c) Üye ülkeler arasında ticaret önemli ölçüde etkilenmelidir. Teşebbüsler arasındaki danışıklık; teşebbüslerin, rekabeti ortadan kaldırmak amacıyla görüş birliği içerisinde olmaları ve buna uygun olarak hareket etmeleri şeklinde tanımlanmaktadır. Bu incelemede danışıklığı oluşturan haller; 'Anlaşmalar', 'Teşebbüs Birlikleri Kararları' ve 'Uyumlu Eylemler' olarak ele alınmıştır. Topluluk Rekabet Hukuku, Teşebbüs, Danışıklık, Anlaşma, Teşebbüs Birlikleri Kararı, Uyumlu Eylem, Rekabetin Kısıtlanması, Üye Ülkeler Arası Ticaret , De Minimis, Haklı Sebep, Per Se (Niteliği Gereği İlkesi)

This study is about 'Agreements' and 'Concerted Practices' in European Community Competition Law Article 81(1). 'Decisions by Association of Undertakings' are also examined within the context of this thesis. European Union Competition Law is of great significance with respect to reaching at goals specified in the Treaty that established the Community. The Treaty was aiming at creating Europe based on liberal economy. In this regard, setting up an effective competition system is crucial for creating 'Common Market'/ 'Single Market'. Articles 81-88 of the Treaty of Rome regulate competition. These articles cover regulations about undertakings and Member States. As far as Article 81(1) of the Treaty is concerned, all agreements between undertakings, decisions by associations of undertakings and concerted practices which may affect trade between Member States of European Union and which have as their object or effect the prevention or distortion of competition within the Common Market are prohibited. For Article 81(1) to apply, there are three essential conditions; a) existence of some form of collusion in the form of an agreement between undertakings, or a decision by an association of undertakings, or a concerted practice, b) which may affect trade between Member States; and c) which must have as its object or effect the prevention, restriction or distortion of competition within the Common Market. Collusion arises when undertakings substitute a form of coordination for the risks of competition. Collusion exists in three forms: Agreements, Decisions and Concerted Practices. Key words: Community Competition Law, Undertaking, Collusion, Agreement, Decision by Association of Undertakings, Concerted Practice, Restriction of Competition, Trade between Member States, De Minimis, Rule of Reason , Per Se Rule
Keywords: Avrupa Topluluğu